ASSOCIATION BETWEEN ELEVATED PHASE ANGLE AND REDUCED RISK OF CHRONIC KIDNEY DISEASE PROGRESSION IN TYPE 2 DIABETES - Low, Serena; Pek, Sharon; Ang, Keven; Subramaniam, Tavintharan; Sum, Chee Fang; Lim, Su Chi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Phase angle (PhA) is a bioelectrical impedance analysis parameter defined as the angle of the vector formed by the body’s resistance and reactance. It indicates nutritional status, with higher levels signifying healthier cell membrane and higher muscle mass. Currently, the association between PhA and chronic kidney disease (CKD) progression is unknown. Pigment epithelium-derived factor(PEDF) has anti-oxidant, anti-angiogenic and anti-inflammatory properties, and its circulating level may be elevated in CKD. We investigated the association between PhA and CKD progression, and the possible mediation of PEDF in this association among Type 2 Diabetes(T2D) patients. METHODOLOGY We conducted a prospective study on 868 patients (mean age 58.1 ± 8.6 years) from SMART2D cohort. PhA was measured using bio-impedance analysis. CKD progression was defined as deterioration across KDIGO estimated glomerular filtration rate(eGFR) categories with ≥25% decrease from baseline. Enzyme-linked immunosorbent assay was used to quantitate PEDF. We examined the association between PhA and CKD progression using Cox proportional regression, adjusting for demographics, clinical parameters and medications. This research has been approved by an ethical committee. RESULTS After a follow-up period of 8.6 years, 40.3% of participants had CKD progression. PhA is inversely associated with CKD progression with a hazard ratio(HR) of 0.69 (95% CI 0.61-0.79; p<0.001). The inverse association persists in fully adjusted analysis with HR 0.78 (95% CI 0.67-0.91;p=0.001). Binary mediation analysis revealed that PEDF accounted for 13.7% of association between PhA and CKD progression (p=0.028). CONCLUSION Our findings have revealed a previously unobserved association between higher PhA and reduced risk of CKD progression. This may pave the way for future studies on the role of PhA in monitoring renal deline.